Fertility-Sparing Treatment for Endometrial Cancer or Atypical Endometrial Hyperplasia Patients With Obesity - Chen, Junyu; Cao, Dongyan; Yang, Jiaxin; Yu, Mei; Zhou, Huimei; Cheng, Ninghai; Wang, Jinhui; Zhang, Ying; Peng, Peng; Shen, Keng (Frontiers in Oncology, 2022)
Objective: To evaluate the efficacy and prognosis of fertility-sparing treatment on endometrial cancer (EC) and atypical endometrial hyperplasia (AEH) patients with BMI ≥30 kg/m2. Methods: 102 EC or AEH patients with obesity who received fertility-preserving therapy in the Department of Obstetrics and Gynecology, Peking Union Medical College Hospital were included in our study. All patients were followed up regularly. Clinical characteristics, treatment outcomes, adverse events, and reproductive outcomes were collected and analyzed. Results: A total of 88 (86.3%) patients achieved complete response (CR), 92.5% in AEH and 82.3% in EC, with the 6 months (3-12 months) median CR time. High remission rates were found in patients who received Gonadotropin-releasing hormone agonist (GnRHa) based regimen were younger than 35 years old and lost more than 10% of their weight. Fifteen (17.0%) women had developed recurrence with the median recurrence time of 26 (8-52) months. Patients who received GnRHa regimen, lost more than 10% weight, received maintenance therapy or conceived during the follow-up period had a low probability of recurrence. Of the patients with CR, 57 women attempted to get pregnant and 16 (28.1%) patients became pregnant, 7 (12.3%) of them successfully delivered and 4 (7.0%) were in pregnancy, while 5 (8.8%) of them miscarried. Conclusion: For obese patients with EC and AEH, fertility-preserving treatment can still achieve a promising response. Weight loss of more than 10% has a positive influence on response, recurrence, as well as pregnancy rates. GnRHa could be an option for obese women due to the less effect on weight gain compared to progestin therapy.